Caregiving Under Social Expectations: An Analysis of Social Media Comments - Bagyura, Márton (Technium Social Sciences Journal, 2025)
Informal caregiving plays a central role in elder care, particularly in Hungary, where emotional bonds, cultural expectations, and religious norms strongly influence caregiving practices. This study aims to explore the motivations behind informal caregiving in Hungary, with a focus on emotional, social, cultural, and religious dimensions. A qualitative content analysis was conducted on publicly available Facebook comments related to elder care in Hungary. The analysis aimed to identify recurring themes and patterns in caregivers’ expressions of motivation and experience. The study revealed a complex interplay of intrinsic motivations—such as love, personal fulfillment, and moral obligation—and extrinsic pressures, including societal expectations, perceived duty, and religious obligations. Caregivers often cited deep emotional attachment and a strong sense of filial responsibility. However, these motivations were frequently accompanied by reports of emotional, physical, and financial strain. Cultural ideals like “caring with joy” and reliance on religious faith served as both sources of strength and added pressure, often discouraging the pursuit of external assistance. The findings highlight the dual nature of caregiving motivations in Hungary, where intrinsic rewards coexist with significant burdens exacerbated by cultural and religious expectations. To prevent caregiver burnout and improve support, policies must be culturally sensitive and recognize both the value and the challenges of informal caregiving. This study contributes to international caregiving literature by underscoring the role of cultural context in shaping caregiving experiences.i